Necrotizing Enterocolitis: Old Problem with New Hope - Shu-Fen Wu; Michael Caplan; Hung-Chih Lin (Pediatrics and Neonatology)
The incidence of necrotizing enterocolitis (NEC) and mortality rate associated with this disease are not decreasing despite more than three decades of intensive research investigation and advances in neonatal intensive care. Although the etiology of NEC is not clearly elucidated, the most accepted hypothesis at present is that enteral feeding in the presence of intestinal hypoxia-ischemia-reperfusion, and colonization with pathogens provokes an inappropriately accentuated inflammatory response by the immature intestinal epithelial cells of the preterm neonate. However, delayed colonization of commensal flora with dysbiotic flora with a predominance of pathologic microorganisms plays a fundamental role in the pathogenesis of NEC. Recent studies have further identified that NEC infants have less diverse flora compared to age-matched controls without NEC. Increased gastric residual volume may be an early sign of NEC. An absolute neutrophil count of <1.5 × 109/L and platelets below 100 × 109/L are associated with an increased risk for mortality and gastrointestinal morbidity. Nonspecific supportive medical management should be initiated promptly. Sudden changes in vital signs such as tachycardia or impending shock may indicate perforation. A recent meta-analysis investigating using probiotics for prevention of NEC with a total of 2176 preterm very low birth weight infants found a success rate of just 1/25. Careful monitoring of the residual volume, and of serious changes in hemograms and vital signs may help in early diagnosis and prediction of when to perform medical or early surgical intervention. In term of prevention, administration of oral probiotics containing Bifidobacterium and Lactobacillus is a simple and safe method that attempts to early establish of commensal flora balance to inhibit pathogenic flora and an inflammatory response.